Spatial variation and associated genes of total hair follicle density in goats - Jipan Zhang; Ziyi Chen; Siyuan Zhang; Guoqiu Li; Xingqiang Fang; Yongju Zhao (Animal Bioscience, 2025)
Objective Improving total hair follicle density (THFD) can directly result in increased fiber yield in cashmere goats. However, its phenotypic and genetic characteristics remain poorly understood. This study aimed to investigate the spatial distribution and associated genes of THFD in goats. Methods A large-scale histological image analysis was conducted on 791 skin samples to characterize the spatial distribution of THFD at the local-site (n = 7), body-side (32 sites, n = 224), and whole-body (14 sites, n = 560) levels. Additionally, transcriptome sequencing was performed on 18 skin samples to identify genes associated with THFD. Results The unique structure of the hair follicle group leads to an uneven distribution of hair follicles, resulting variation in THFD at the local-site. THFD exhibited a gradient pattern throughout the body, characterized by elevated values in the scapular region and decreased values in the abdominal region. THFD showed uneven distribution across the whole-body, with a consistent pattern observed in Inner Mongolia cashmere goats, Dazu black goats and their F1 hybrids (DBG♂ × IMCG♀). Through the integration of differential gene expression analysis, trend analysis, weighted correlation network analysis, Venn analysis, and literature review, four core genes (GJA1, DSP, CDH3, and PER1) were identified. These genes showed high and specific expression in skin tissue and demonstrated a significant response to changes in THFD. Conclusion This study thoroughly characterized the spatial variation of THFD at the local-site, body-side, and whole-body levels in order to gain a better understanding of genetic characterization, associated genes and spatial variation. Additionally, we have identified four genes that are associated with THFD. These findings provide an important reference for the subsequent development and utilization of THFD genes in cashmere goats.